Analisis Life Cycle Assessment (LCA) pada Instalasi Unit Gas Turbine Generator Area Gas Processing Facility (GPF) di Perusahaan Pengolahan Minyak Dan Gas Bumi, Jawa Timur - Santosa, Dwi Teguh; Ni’am, Achmad Chusnun; Maulana, Chandra Mukti Sri (Teknik Lingkungan, Institut Teknologi Adhi Tama Surabaya, 2025)
The oil and gas production process presents significant risks of environmental pollution and human health hazards while also requiring substantial energy consumption. Therefore, a Life Cycle Assessment (LCA) is conducted to estimate potential environmental effects throughout the production cycle, from raw material processing to the final product. This study employs a gate-to-gate LCA approach, utilizing data from the Compendium of Greenhouse Gas Emissions Methodologies for The Natural Gas and Oil Industry – API 2021 and processed using SimaPro 9.0.0.48. The functional unit is 1 MMSCF (Million Standard Cubic Feet). The LCA framework follows four key stages: goal and scope definition, Life Cycle Inventory (LCI), Life Cycle Impact Assessment (LCIA), and data interpretation. Impact category assessment is conducted using SimaPro 9.0.0.48 with methodologies including CML-IA baseline V3.05_EU25 and Eco-Indicator 99 (H) V2.10. The impact categories assess Global Warming, Acidification, Human Toxicity, Eutrophication, and Photochemical Oxidation within the Gas Turbine Generator System. Findings from this study can support the company’s environmental management and energy efficiency initiatives. The research results for the Gas Turbine Generator - GPF unit indicate that the oil and gas processing production generate the following emissions per 1 MMSCF: 1,986.78 kg CO₂ eq (Global Warming Potential ≥ 30%); 1.01686 kg SO₂ eq (Acidification ≥ 40%); 0.04813 kg C₂H₄ eq (Photochemical Oxidation ± 40%); 0.11865 kg PO₄ eq (Eutrophication ± 40%); Land Use Impact ≥ 10%; and Ecotoxicity ≤ 10%. Keywords: Gas Turbine Generator, Life Cycle Assessment, SimaPro 9.0.0.48, CML-IA baseline V3.05_EU25, Eco-Indicator 99 (H) V2.10